Estimating aerosol characteristics from solar irradiance measurements at an urban location in southeastern Spain. Issue 4 (25th February 2014) - Foyo‐Moreno, I.; Alados, I.; Antón, M.; Fernández‐Gálvez, J.; Cazorla, A.; Alados‐Arboledas, L.
Abstract Under cloudless conditions aerosols are the main atmospheric components responsible for direct effects on solar radiation. Measurements of aerosol optical properties along with simultaneous measurements of solar irradiances (global –G– and diffuse –D–) were recorded at an urban site (Granada, Spain) to characterize the radiative effect of atmospheric aerosols from 2006 to 2008. The selection of cloudless conditions was made considering cases with 0 oktas. To avoid cloud contamination, a restricted data set with clearness index larger than 0.65 and maximum D of 200 W/m2 was used. The analysis was performed evaluating G, D, and IN (direct normal irradiance) and the ratios between them in association with aerosol optical depth (AOD) at 675 nm. Results show an aerosol forcing efficiency of −279 ± 21 W/m2 per unit of AOD at 675 nm at 15° solar zenith angle and a maximum value in June for monthly mean aerosol radiative forcing of −23 ± 7 W/m2. Large dependency was shown of the ratios D/G and D/IN which increased with increasing AOD, while IN/G decreased. On the other hand, the ratio D/IN was the most reliable parameter to estimate AOD with a coefficient of determination of 0.94; the empirical relationship obtained was validated using an independent data set obtaining 2.5% mean bias deviation and 13.5% root‐mean‐square deviation. This relationship constitutes an alternative tool for estimating AOD from routine irradiance measurements available from numerous radiometric stations worldwide.